Conceptual and Normative Aspects of International Management - Kolde, Endel J.; Hill, Richard E. (Academy of Management Journal, 1967)
A multinational enterprise operates in a plurality of dynamic environments. Its organizational structure, therefore, must consist of two parts: (1) a nationally and culturally decentralized base designed to deal with pluralistic conditions through strong, autonomous subentities and (2) a centralized superstructure to achieve coordination throughout the whole. Coordination is predicated on effective international communication ? both its linguistic and non-linguistic aspects. Good communication, in turn, requires comparability of standards, rapid feedback and multiple management.